The Influence of Islamic Banking Development on Financial Sector Economic Growth and Its Impact on the Human Development Index (HDI) and Poverty - Nani Almuin; Ahmad Rodoni (Jurnal Multidisiplin Indonesia, 2025)
The purpose of this study is to examine the impact of overall financing, total assets, earnings, total capital, inflation, and the Islamic Banking Service Index (SBSI) on Indonesia's economic expansion, as well as how poverty and the Human Development Index (HDI) are affected by economic expansion. Panel data regression analysis is the methodology employed in this study. The Central Statistics Agency and the Financial Services Authority provided the panel data, which covers 13 Islamic banks in Indonesia from 2014 to 2023. The results show that earnings, total capital, inflation, and SBSI have significant effects on economic growth, whereas total financing and total assets do not significantly influence economic growth. Economic growth, in turn, affects poverty levels and the HDI.